Model of the inertial and optical navigation system of the unmanned aerial vehicle - A. M. Kovalenko; A. A. Shejnikov (Системный анализ и прикладная информатика, 2020)
In article approaches to creation of the complex inertial and optical navigation system of the short-range tactical unmanned aerial vehicle are considered. Algorithms constant and periodic (in intermediate points of a route) are offered correction of the platformless onboard inertial navigation system. At integration of information on parameters of the movement of the unmanned aerial vehicle (received from the considered systems) the invariant loosely coupled scheme of data processing on the basis of the expanded filter of Kallman was used that allowed to lower significantly a systematic component of an error of the platformless inertial navigation system. Advantages of the complex inertial and optical navigation system when ensuring flight of the unmanned aerial vehicle in an area of coverage of means of radio-electronic fight of the opponent are shown. The results of modeling confirming a possibility of ensuring precision characteristics of the inertial and optical navigation system in the absence of signals of satellite radio navigational systems are presented.